Analysis of The Structure and Meaning of The Lyrics Song of Adeles 30th Album “Struggle of Love” - Edmundus Rifan (English Education Postgraduate Program, Universitas Negeri Manado, 2023)
Analysis of the Structure and Meaning of the Lyrics Song of Adele’s 30th Album “Struggle of Love”. Paper. Maumere: Faculty of Social Sciences Education and Humanities. IKIP Muhammadiyah Maumere. 2023. This research aims to know and explain the structures and the meanings of song’s lyrics of Adele’s 30th album. There are two focuses of research namely physical and inner structure and meaning. The method of research used descriptive qualitative. In this research, there are two data sources, namely: primary and secondary data. For data collection, the researcher used interpretation of written material according to published notes, and articles. Based on the researcher conducted by the researcher, some important things can be found it, namely Adele’s songs contain a lot of structure and meaning. The results of the analysis found that in Adele’s song especially in 30th album, there are two big points. The points are: structure and meaning. The physical structure of Adele’s songs contains a lot of diction, figurative language, and imagery, basically that of the seventh mostly used three important parts of the physical structure. In terms of the inner structure of Adele’s songs there are important elements in them namely: themes, tones, feeling and mandate that are so diverse and aesthetically pleasing. Basically, of all that song that exist, not all song contains important points in the inner structure but only a few songs